2017
DOI: 10.1007/s12550-017-0289-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of deoxynivalenol (DON) and its microbial biotransformation product deepoxy-deoxynivalenol (DOM-1) on a trout, pig, mouse, and human cell line

Abstract: Deoxynivalenol (DON), a trichothecene produced by various Fusarium species, is one of the most prevalent food- and feed-associated mycotoxins. The effects of DON and deepoxy-deoxynivalenol (DOM-1) were assessed in five different cell lines from different tissues and species starting from the first line of defense, the trout gill (RTgill-W1) and pig intestinal cells (IPEC-1 and IPEC-J2) over immune cells, as second line of defense (mouse macrophages RAW 264.7) to human liver cells (HepG2). Viability was assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 78 publications
(45 reference statements)
4
36
0
2
Order By: Relevance
“…Based on this, we investigated the protective effect of n‐3 PUFA on intestinal cell injury and barrier function impairment after DON challenge, and to explore its molecular mechanism(s) using the IPEC‐1 cell model. DON is a mycotoxin with strong cytotoxicity, which mainly exerts toxic effects in gastrointestinal tract and immune system and can lead to intestinal damage …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on this, we investigated the protective effect of n‐3 PUFA on intestinal cell injury and barrier function impairment after DON challenge, and to explore its molecular mechanism(s) using the IPEC‐1 cell model. DON is a mycotoxin with strong cytotoxicity, which mainly exerts toxic effects in gastrointestinal tract and immune system and can lead to intestinal damage …”
Section: Discussionmentioning
confidence: 99%
“…DON is a mycotoxin with strong cytotoxicity, which mainly exerts toxic effects in gastrointestinal tract and immune system and can lead to intestinal damage. 26 Cell viability and number serve as criteria that reflect cell growth, and amount of LDH released into the culture medium from damaged cell membranes reflects cell damage. In our study, expectedly, DON challenge decreased cell viability and cell number, and increased LDH activity, which suggested that DON caused epithelial cell damage.…”
Section: Discussionmentioning
confidence: 99%
“…In the present trial, trout were fed a non-contaminated diet (for three weeks) prior to the [ 3 H]-DON tube feeding. It has been reported that chronic exposure to DON might cause the destruction of tight junctions [20,21] leading to increased DON absorption. We assume that in the present study, the trouts' physiological conditions due to the three weeks acclimation were optimal and intestinal barrier would not be much impacted by the short period of DON exposition (maximum of twenty-four hours).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, HCT-8 or IPEC-1 cell-based barrier was assessed due to its rapid formation of epithelial monolayer among the colorectal adenocarcinoma-derived enterocytes. In particular, IPEC-1 cells have been extensively used as the non-tumorigenic enterocyte model of DON exposure ( 17 , 33 , 34 ). The colorectal adenocarcinoma-derived enterocytes were cultured in RPMI 1640 medium supplemented with 10% heat-inactivated FBS, 50 U/ml penicillin, and 50 µg/ml streptomycin (all from Welgene, Daegu, South Korea) in a 5% CO 2 humidified incubator at 37°C.…”
Section: Methodsmentioning
confidence: 99%